2019
DOI: 10.3389/fpsyg.2019.00154
|View full text |Cite
|
Sign up to set email alerts
|

Goal Pursuit in Organizational Health Interventions: The Role of Team Climate, Outcome Expectancy, and Implementation Intentions

Abstract: In taking a goal pursuit perspective into account, the present study examined associations between the context, process and outcome evaluation of an organizational health intervention (OHI) implemented within 29 teams in a hospital setting. In doing so, team climate for innovation as a context factor was measured at baseline (N = 529). Four to six weeks after baseline, N = 250 team representatives participated in a 4-day workshop. During the workshop employees formulated collective goals as action plans to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 83 publications
(134 reference statements)
0
14
1
Order By: Relevance
“…This high satisfaction is likely to strengthen their trust in the efficacy of the action plans, which becomes apparent in high outcome expectancies for the workshop. Lehmann et al (2019) showed for example that if-then plans -i.e., the workshop output in form of concrete action plans -were related to the perception of intervention success.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This high satisfaction is likely to strengthen their trust in the efficacy of the action plans, which becomes apparent in high outcome expectancies for the workshop. Lehmann et al (2019) showed for example that if-then plans -i.e., the workshop output in form of concrete action plans -were related to the perception of intervention success.…”
Section: Discussionmentioning
confidence: 99%
“…The results also support the assumption that participants who appraise a workshop as favorable also have high outcome expectancies. This relationship is partially mediated by satisfaction with the output developed during a workshop: Participants who rate a workshop as favorable are also more likely to be satisfied with the developed action plans, which in turn leads to high outcome expectancies: Outcome expectancies are known to be related to the perception of intervention success ( Fridrich et al, 2016 ; Lehmann et al, 2019 ). A study utilizing a preliminary, not yet-validated version of the WASC aggregated on team level revealed that outcome expectancies – rather than workshop appraisals – were directly relevant for changes in working conditions, but also indicated that positive appraisal of the workshops was related to changes in affective activation at work ( Füllemann et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing cooperation by forming cIIs could thus be highly beneficial in work contexts (Thürmer et al, 2015a;Gagné, 2018). Although limited data is available on this question (Lehmann et al, 2019), research on social dilemmas and social loafing has proven highly influential in organizational teams (Stouten and Liden, 2020), and II effects have been observed in organizational contexts, such as adherence to new workplace regulations (Holland et al, 2006) and making entrepreneurial decisions (Adam and Fayolle, 2015;van Gelderen et al, 2017). It is, therefore, likely that cII effects on cooperation generalize to organizational settings (Thürmer et al, 2015a).…”
Section: Implications For Cooperation In Groupsmentioning
confidence: 99%